2012
DOI: 10.1186/1471-2334-12-138
|View full text |Cite
|
Sign up to set email alerts
|

The seroepidemiology of Immunoglobulin G antibodies against pertussis toxin in China: a cross sectional study

Abstract: Background Pertussis is a reported vaccine-preventable respiratory disease in China. Because the routine laboratory methods for diagnosis are not in use, the reported cases are mainly in infants with classical paroxysmal cough and the true incidence related to pertussis is most likely under estimated. In China, however, few studies have attempted to address this issue. The purpose of this cross sectional study was to estimate the incidence rates using the method of sero-epidemiology of immunoglobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 19 publications
7
37
0
Order By: Relevance
“…Highest mean antibody levels (18.44 IU/ml) and sero-positivity (11.43%) was reported in 13–19 age group which suggests peak incidence of B. pertussis infection in this age group. This finding is very much similar to the findings of the present study [26]. …”
Section: Discussionsupporting
confidence: 93%
“…Highest mean antibody levels (18.44 IU/ml) and sero-positivity (11.43%) was reported in 13–19 age group which suggests peak incidence of B. pertussis infection in this age group. This finding is very much similar to the findings of the present study [26]. …”
Section: Discussionsupporting
confidence: 93%
“…We found that 4.3% of subjects not vaccinated with Tdap in the last 6 months had serologic evidence of recent pertussis infection, and that the annual pertussis infection rate among subjects not vaccinated in the last 5 years was 10.5–17.5%. This rate is 1000-fold higher than the annual incidence of reported cases for the general U.S. population in 2014 20 , consistent with other seroprevalence studies that have found pertussis to be vastly underreported 15,18,19 . It is also 10-fold higher than the seroprevalence rate reported from a study among healthy American adolescents and adults in 1997–1999 4 .…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have shown that mean anti-PT IgG levels drop to 9–14 units/ml by 18–36 months after Tdap vaccination 13,16,17 . In addition, other studies have used anti-PT IgG levels ≥30 units/ml to diagnose recent pertussis infections in subjects not vaccinated against pertussis for ≥2.5 years 18,19 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, B. pertussis strains isolated in the two provinces had identical genotypes and PFGE profiles, suggesting that B. pertussis with ptxA1 ptxP1 and BpFINR9 or BpSR23 are circulating in this country. Our data also indicate that the incidence of pertussis is most likely underestimated in China (7,8).…”
mentioning
confidence: 62%